PENILAIAN DAN ANALISIS CORPORATE ENTREPRENEURSHIP CULTURE UNTUK MENINGKATKAN TINGKAT EFEKTIVITAS PERUSAHAAN DI PT. PDAM TIRTA DHARMA BANYUMAS KABUPATEN BANYUMAS - Wartiyah, Wartiyah; Daryono, Daryono (Faculty of Economics and Business Universitas Jenderal Soedirman, 2012)
Entrepreneurship is an appropriate answer to PT PDAM Tirta Dharma Banyumas to deal with its changing environment. It is also in line with PT PDAM Tirta Dharma Banyumas’s vision, mission, target, and strategy. The objectives of this final project are to analyze key dimensions of intrapreneurship within PT PDAM Tirta Dharma Banyumas, and to analyze the importance of entrepreneurial leadership and its execution in PT PDAM Tirta Dharma Banyumas. This study was conducted through survey method, using questionaires EOS and ELQ which distributed to PT PDAM Tirta Dharma Banyumas’s employees. EOS is used to measure the entrepreneurial environment at PT PDAM Tirta Dharma Banyumas. Its key dimensions are My Company, Strategic Planning, Support for New Idea, Market Intelligence, Risk Aversion, Speed, Flexibility, The Future, and Personal Orientation.